ASSESSMENT OF HIV VIRTUAL STRATEGY ON LANE IN THE COVID PANDEMIC 19 - Erna Agustina (International Jurnal of Education Schoolars, 2020)
In the midst of a tense and constantly increasing pandemic, the government is now automatically a policy of social restrictions to tackle transmission, not only that coaching budget constraints are changing. This certainly becomes an obstacle in carrying out health assistance which has so far been carried out with face-to-face meetings so as to require fairly high mobility, so that assistance becomes intensive in communicating and supervising, ensuring that ODHA and their children's assistance remain compliant with health regulations. Banyuwangi District Child Protection Commission (KPA) has implemented a new strategy, so that health assistance, especially prevention of HIV Aids prevention, continues with maximum results. Among the strategies that have been carried out are with Virtual Online. This study uses descriptive qualitative research methods with a phenomenological approach to be able to see how effective the adaptation of the assistance model has been done. Virtual online that has been carried out by KPA of Banyuwangi Regency shows the effectiveness of mentoring to the maximum compared to face to face. This shows that this assistance model is quite effective to be carried out in the pandemic covid era 19.